Prevalence of cardiorenal syndrome in patientsadmitted to a tertiary hospital - Dr.S.SAKTHI SELVA KUMAR,; Dr.SIVAKUMAR, (International Journal of Pharma and Bio Sciences, 2016)
Many Patients have different degrees of cardiac and renal dysfunction. Mortality, morbidity and cost of care greatly increase when these two coexist. A cohort study was conducted on 800 patients admitted from (June 2014- June 2015) to evaluate the prevalence of the Cardio renal syndrome (CRS) and clinical features. Out of 800 patients, 200 (25%) were diagnosed as having CRS and classified into five types. CRS type 1 was associated with higher age (79.9 ± 8.9 years) and accounted for 61.5% of all deaths (p < 0.001), representing a risk factor for mortality (OR 4.23, 95% CI 1.8–10). Congestive cardiac failure was significantly different among the five CRS types (p < 0.0001) with a greater frequency in type 1 patients. Infectious diseases were more frequent in CRS types 1, 3 and 5 (p < 0.05). Community-acquired infections were more frequent in CRS types 1 and 5 (p < 0.05). Pneumonia (Nosocomial and Community acquired) presented more in CRS types 1 and 5 compared to others. (P< 0.01), and the distribution of community-acquired pneumonia was different among the classes (p < 0.01) with a higher frequency in CRS types 1, 3 and 5. The worst renal function was recorded in CRS types 3 and 4.CKD was significantly different among the five CRS types (p < 0.0001) with the highest prevalence in CRS type 3 (50%, 16 of 32 patients). CRS is a condition which is more frequently observed in the clinical practice but underdiagnosed. Identifying the predisposing trigger factors, like infectious diseases, mainly in the elderly, plays an important role in reducing morbidity and mortality. An early recognition can be useful to therapy and to prevent complications.